Wintering Ruffs Philomachus pugnax are not pest of Rice Oryza spp. in Nigeria’s Sahelian Wetlands - Ezealor, Augustine U; Giles, Jr, Robert H (Wildfowl, 1997)
The food and feeding habits of Ruffs wintering in a Nigerian Sahelian wetland were investigated by analyzing their gut contents and observing their foraging habits in the field. Although rice constituted a large proportion (30.5-37.8%) of Ruff diet during most of the wintering period, the species could not be considered an important vertebrate pest of rice in the area, because most of the consumed grain was waste and residue grain from harvesting and threshing operations. In addition, the depth of water in rice fields and the availability of invertebrates made unlikely Ruff depredation of rice during the early wintering period.